THE ROLE OF GUT MICROBIOTA DYSBIOSIS IN THE PATHOGENESIS AND PROGRESSION OF CHRONIC INFLAMMATORY BOWEL DISEASE IN CHILDREN (LITERATURE REVIEW) - Farmonov Samandar Anvar o‘g‘li; Ro‘ziyev Javlonbek Orifjon o‘g‘li; Zayniddinov Og‘abek Farxod o‘g‘li; Egamberganova Mohimjon Mahmudjon qizi; Saparklicheva Ayzada Rahman qizi (TADQIQOTLAR, 2026)
Abstract Chronic inflammatory bowel disease (IBD), encompassing Crohn’s disease (CD) and ulcerative colitis (UC), represents a growing burden in the pediatric population, with gut microbiota dysbiosis increasingly recognized as a central pathogenic driver. This review synthesizes current evidence linking gut microbial imbalance—characterized by reduced diversity, depletion of short-chain fatty acid (SCFA)-producing commensals, and expansion of pro-inflammatory species—to mucosal barrier dysfunction, immune dysregulation, and chronic intestinal inflammation in children. Persistent dysbiosis activates innate immune pathways including Toll-like receptors (TLRs) and the NLRP3 inflammasome, perpetuating a cycle of epithelial injury, cytokine release, and fibrotic remodeling. Early-life disruptions to microbial colonization, including antibiotic exposure, cesarean delivery, and formula feeding, further predispose children to IBD onset. Despite growing mechanistic understanding, pediatric-specific longitudinal microbiome data remain scarce, highlighting the urgent need for validated biomarkers and microbiota-targeted therapeutic strategies. Interventions such as dietary modulation, fecal microbiota transplantation (FMT), and probiotic supplementation offer promising avenues to restore microbial homeostasis and preserve intestinal integrity in affected children.